Directional protection scheme using impedance approach for transmission lines - Ahmed R. Adly; Mahmoud A. Elsadd; Mahmoud M. Elgamasy; Omar F. Fadl; Mohamed A. Tolba (Scientific Reports)
Abstract Identifying the direction of fault is an essential mission of the transmission line protective scheme. This paper discusses a direction protective technique based on a positive impedance approach. The samples of the instantaneous positive sequence voltage component and the instantaneous positive sequence current component are used to determine the impedance approach and complete the Z matrix values. The fault direction can be determine using Z matrix values. Different configurations of the power system are utilized to examine the proposed protective scheme. Software ATP-EMTP (Simulation experiments) verified the feasibility of the presented scheme. To verify the capability and accuracy of presented scheme, it is examined by many fault scenarios such as high fault resistance, far end fault, cross-country fault, power flow change, single pole tripping, CT saturation and noise impact. In addition, the validity of the presented scheme is compared with other protection directional schemes.